Tinjauan Luas Pengungkapan Corporate Social Responsibility (CSR) : Tata Kelola, Struktur Kepemilikan, dan Kinerja Perusahaan - Ming Chen; andrew gunawan (Owner : Riset dan Jurnal Akuntansi, 2025)
This study investigates the extent of Corporate Social Responsibility (CSR) disclosure among banking companies in Indonesia, focusing on the influence of corporate governance (proxied by the proportion of independent commissioners), ownership structure (foreign ownership), and firm performance (return on assets). The research is grounded in stakeholder theory and information asymmetry theory, which argue that effective governance and transparency serve to legitimize a firm's actions in the eyes of stakeholders. The sample consists of Indonesian banking firms listed on the Indonesia Stock Exchange (IDX) during 2020–2023, selected using purposive sampling. Using panel data regression with the Random Effect Model (REM), the findings reveal that none of the three independent variables independent commissioners, foreign ownership, and profitability have a statistically significant effect on CSR disclosure levels. These results suggest that the expected positive relationships between governance, ownership, and performance with CSR disclosure may not apply uniformly in the banking sector. Institutional pressures, short-term investor orientation, and symbolic compliance may account for these inconsistencies. The study highlights the need for more comprehensive governance mechanisms and stakeholder engagement strategies to enhance CSR disclosure practices in Indonesian banks.